Disease Activity in Psoriatic Arthritis: Comparison of the Discriminative Capacity and Construct Validity of Six Composite Indices in a Real World - Salaffi, Fausto (Hindawi Publishing Corporation, 2014)
Objective. To compare, “in a real world,” the performance of the most common composite activity indices in a cohort of PsA patients. Methods. A total of 171 PsA patients were involved. The following variables were evaluated: peripheral joint assessment, patient reported of pain, physician and patient assessments of disease activity, patient general health status, dactylitis digit count, Leeds Enthesitis Index, Health Assessment Questionnaire (HAQ), physical and mental component summary score of the Medical Outcome Survey (SF-36), Psoriasis Area and Severity Index (PASI), Dermatology Life Quality Index, C-reactive protein (CRP), and erythrocyte sedimentation rate (ESR). To measure the disease activity, the Disease Activity Score (DAS28-ESR and DAS28-CRP), Simple Disease Activity Index (SDAI), Composite Psoriatic Disease Activity Index (CPDAI), disease activity in psoriatic arthritis (DAPSA), and Psoriatic Arthritis Disease Activity Score (PASDAS) have been calculated. The criteria for minimal disease activity (MDA) and remission were applied as external criterion. Results. The ROC were similar in all the composite measures. Only the CPDAI showed less discriminative ability. There was a high degree of correlation between all the indices (P < 0.0001). The highest correlations were between DAPSA and SDAI (rho = 0.996) and between DAPSA and DAS28-CRP (rho = 0.957). CPDAI, DAPSA, and PASDAS had the most stringent definitions of remission and MDA category. DAS28-ESR and DAS28-CRP had the highest proportions in remission and MDA. Conclusions. Although a good concurrent validity and discriminant capacity of six disease activity indices were observed, the proportions of patients classified in the disease activity levels differed. In particular, the rate of patients in remission was clearly different among the respective indices.